Evaluating the implementation of UHC policy through the strengthning of primary health care and refferral system governance in Indonesia: A literature review - Tuanku Banang Rabbani Imsyaamru; Rizky Khaeran; Rizwandy Wasir (PT WIM Solusi Prima, 2026)
The implementation of Universal Health Coverage (UHC) in Indonesia through the National Health Insurance (JKN) program has significantly expanded population coverage and improved access to healthcare services. However, challenges remain in ensuring effective service utilization, particularly in primary healthcare and referral system governance. Key issues include limited capacity of primary healthcare facilities, high rates of inappropriate referrals, and weak coordination among healthcare providers. This study aims to evaluate the implementation of the UHC policy in Indonesia through strengthening primary healthcare and referral system governance, and to identify barriers and enabling factors affecting its implementation. This study uses a qualitative approach with a literature review design. The study population consists of scientific articles, policy reports, and official government documents related to UHC implementation in Indonesia. The selected literature sample was obtained through purposive sampling based on topic relevance, publication period within the last ten years, and source credibility. The study variables include healthcare access, primary healthcare capacity, referral system, and UHC policy implementation. Data were collected through a systematic search of Google Scholar and PubMed databases and analyzed using thematic analysis and critical synthesis. The findings indicate that despite high JKN membership coverage, service quality and sustainability remain suboptimal due to human resource shortages, limited infrastructure, and ineffective tiered referral mechanisms. In conclusion, the success of UHC implementation depends not only on expanding insurance coverage but also on strengthening primary health care capacity and improving referral system governance to achieve effective, equitable, and sustainable health services.